The Difficulties of the opening text between changing and collecting reading in poem (city without rain): The Difficulties of the opening text between changing and collecting reading in poem (city without rain) (Journal of the College of Education for Women, 2019)
AbstractThis research deals with the technical of opening text during the criticalstudy about the poem of Al- ssiyab which is named ( city with out rain)We chose this poem also to make connection with the western criticaltheories.Our study aims to explain the act of opening texts and critics and itsmethods and directions in modern Arabic poetry.It also aims to show the differences in the point of view between criticsand poetries.The research depends on dimension vision of selective, and descriptive.